Arctic freshwater natural capital in the Nordic countries - Soile Oinonen; Johanna Pohjola; Jani Salminen; Virpi Lehtoranta; Tuija Mattsson; Sari Väisänen; Luke Dodd; Gerdur Stefansdottir; Eivind Aronsen; Marcus Carson; Tea N\~ommann; Doan Nainggolan (Arctic freshwater natural capital in the Nordic countries, 2019)
Freshwater resources in the Nordic Arctic: Sectoral demands, pressures, and externalities – Preface – Economic and environmental impact analyses using ecosystem accounting – Arctic freshwaters, ecosystem services and natural capital – – References – Current and potential uses of water accounts Finland – Executive summary – How can freshwater natural accounting be used in governing Arctic freshwater resources? – Current status of environmental accounting in the Nordic countries – Abbreviations.Current indicators of economic growth (e.g., GDP) do not adequately consider sustainability, while environmental indicators alone fail to acknowledge the economic needs of a society. Natural Capital Accounting (NCA) can be the tool that fills the gap separating current economic and environmental indicators. Development of NCA has progressed considerably and is being widely deployed in the Nordic countries, but development and deployment remain uneven. This report provides background on NCA and its associated accounting frameworks, demonstrates the applicability of NCA for sustainably utilizing freshwater resources in the Nordic Arctic and provides recommendations for maximizing the value of environmental accounting as an economic, environmental, and sustainable development tool
urn:nbn:se:norden:org:diva-5446 10.6027/TN2019-505; urn:nbn:se:norden:org:diva-5446; 10.6027/TN2019-505; 557635853